Sustainable nanophysics: Green synthesis production of magnesium oxide nanostructures for advanced biological activity - Hussein, Diyaa Y (Technium: Romanian Journal of Applied Sciences and Technology, 2026)
In this work, a novel green synthesis for producing magnesium oxide nanoparticles (MgO NPs) using three plant extracts— cumin (C. cyminum), pomegranate (P. granatum), and coffee (C. arabica)—for sustainable nanophysics and demonstrating enhanced antibacterial activity against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) and anticancer activity against cervical cancer cells. MgO NPs was characterized by XRD patterns, FESEM images, EDX analysis, FTIR spectrum, and UV-visible spectrum to study the nanophysics (structure and optical) properties. The average crystalline sizes and nanocrystals of MgO NPs prepared using (C. cyminum), (P. granatum), and (C. arabica) extracts were (21.26, 21.39, and 18.32) nm with face-centered cubic (FCC), respectively, as confirmed using XRD patterns. FE-SEM showed the morphology and the particle size of MgO NPs prepared using these extracts indicated mostly spherical and irregularly nanoparticles shaped with (24.95, 19.68, and 13.89) nm, respectively, while EDX analysis confirmed the high purity of Mg and O elements. The FTIR spectrum confirmed the strong absorption peak of MgO NPs prepared using (C. cyminum), (P. granatum), and (C. arabica) extracts were 414 to 646 cm⁻¹, 418 to 648 cm⁻¹, and 419 to 649 cm⁻¹, respectively, by revealing unique Mg–O stretching vibrations. The energy band gaps of MgO NPs prepared using (C. cyminum), (P. granatum), and (C. arabica) extracts were 5.7 eV, 5.9 eV, and 5.8 eV, respectively, as revealed by UV-Vis spectrum. According to this study, gram-positive bacteria (S. aureus) had inhibitory zones of 99.98%, 99.50%, and 68.39%, respectively. The inhibition ratios of gram-negative bacteria (E. coli) were 82.22%, 71.87%, and 68.75%, respectively. Additionally, at a dosage of 1000 µg/mL, MgO NPs prepared using (C. cyminum) extract showed 55.57% cell death against cervical cancer cells (HeLa line), indicating strong anticancer potential.